2018
DOI: 10.1002/jrs.5465
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and polarization dependent Raman spectra of liquid H2O and D2O

Abstract: Polarized Raman spectra of liquid H2O and D2O have been measured over the entire 100 to 4,000 cm−1 vibrational frequency range and 280 to 360 K temperature range. The measured spectra are corrected for wavelength‐dependent detector quantum efficiency and are provided in numerical form to facilitate comparisons with theoretical predictions. Self‐modeling curve resolution is used to decompose the measured spectra into a linear combination of two spectral components whose relative intensities change with temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 62 publications
(120 reference statements)
0
23
1
Order By: Relevance
“…It should be emphasized that both experiments and simulations give almost constant depolarization ratios over the whole OH stretch region in each polarized-HR set. The uniform HR depolarization ratios of the OH stretch are in sharp contrast to the usual Raman depolarization ratios, which show various values from 0.1 to 0.5 in the OH stretch region. , …”
mentioning
confidence: 79%
“…It should be emphasized that both experiments and simulations give almost constant depolarization ratios over the whole OH stretch region in each polarized-HR set. The uniform HR depolarization ratios of the OH stretch are in sharp contrast to the usual Raman depolarization ratios, which show various values from 0.1 to 0.5 in the OH stretch region. , …”
mentioning
confidence: 79%
“…Pattenaude and colleagues presented temperature‐ and polarization‐dependent Raman spectra of liquid H 2 O and D 2 O. The spectral component whose intensity increases with decreasing temperature contains prominent features in both the high‐frequency OH stretch band region and low‐frequency OH···O hydrogen bond stretch band region that resemble those observed in single crystal ice Ih and clathrate hydrates . Ruggiero et al used Raman to study the hydration of the monosaccharides glucose, fructose, and mannose.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…The spectral component whose intensity increases with decreasing temperature contains prominent features in both the high-frequency OH stretch band region and low-frequency OH···O hydrogen bond stretch band region that resemble those observed in single crystal ice Ih and clathrate hydrates. [180] Ruggiero et al used Raman to study the hydration of the monosaccharides glucose, fructose, and mannose. They found that glucose and fructose interact strongly with water, whereas for mannose, a weaker interaction with water and a different behaviour of its anomers, was observed.…”
Section: Metals Carbons and Other Crystalline Materialsmentioning
confidence: 99%
“…To minimize the effects of external water penetration, we introduced a probe of heavy water (D 2 O) to dissolve the model substances applied to the skin. With this probe, the effects of external penetrated water can be eliminated due to different Raman spectral features of OD bond and inherent skin OH bond [33]. Thus, skin water‐related properties can be effectively detected.…”
Section: Introductionmentioning
confidence: 99%